2021
DOI: 10.1136/jclinpath-2021-207440
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p16Ink4aprotein in pleomorphic adenoma and carcinoma ex pleomorphic adenoma proves diversity of tumour biology and predicts clinical course

Abstract: AimsThe aim of the study is to correlate p16Ink4a expression with the clinical courses of pleomorphic adenoma (PA), its malignant transformation (CaexPA) and treatment outcomes.MethodsRetrospective analysis (1998–2019) of 47 CaexPA, 148 PA and 22 normal salivary gland samples was performed. PAs were divided into two subsets: clinically ‘slow’ tumours characterised by stable size or slow growth; and ‘fast’ tumours with rapid growth rate.ResultsPositive p16Ink4a expression was found in 68 PA and 23 CaexPA, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 39 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Such an approach is novel in the context of PA as the previous reports have rather examined selected genes as potentially methylated in PA and/or the subsequent CaexPA and were not related to the differential course of PA [ 22 , 23 , 24 ]. In contrast, in our recent paper, we revealed differences in p16Ink4a protein expression between FGT and SGT PAs and demonstrated that its overexpression is connected to PA proliferation and subsequent malignant transformation to CaexPA [ 21 ].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Such an approach is novel in the context of PA as the previous reports have rather examined selected genes as potentially methylated in PA and/or the subsequent CaexPA and were not related to the differential course of PA [ 22 , 23 , 24 ]. In contrast, in our recent paper, we revealed differences in p16Ink4a protein expression between FGT and SGT PAs and demonstrated that its overexpression is connected to PA proliferation and subsequent malignant transformation to CaexPA [ 21 ].…”
Section: Discussionmentioning
confidence: 74%
“…Recent decades have brought a marked increase in the incidence of salivary gland tumors [ 5 , 12 , 20 ]. Among them, pleomorphic adenomas are the most frequent, and as previously observed, their development may vary in the context of tumor growth rate and malignant transformation [ 12 , 21 ]. On one hand, at the stage of initial diagnosis, both pathologists as well as clinicians are not able to assign the tumor to the fast-growing or slow-growing cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Bartkowiak E. et al showed that human papilloma virus type 16 overexpression was connected with pleomorphic adenoma proliferation and subsequent malignant transformation to carcinoma (carcinoma ex pleomorphic adenoma) [12].…”
Section: Resultsmentioning
confidence: 99%
“…Comparison against PA and SDCDN were both nonstatistically significant (Supplement 2.9). 50,51,62 p16 Five studies (n = 171) reported p16 incidence, 48,[75][76][77][78] with four (n = 134) available for meta-analysis. The reading from the nucleus of malignant p16 cells were used when multiple p16 readings were reported.…”
Section: Prmentioning
confidence: 99%
“…76 Three studies reported on IHC overexpression of p16Ink4a protein, with high and statistically significant heterogeneity between studies. [75][76][77] Tourne et al used an IHC-based quantification score to identify if median p16 expression was lower in PA than CXPA. 48 Two studies reported methylation incidence.…”
Section: Prmentioning
confidence: 99%